AutoSLAM – A policy‐based framework for automated SLA establishment in cloud environments. (30th November 2013) - Baruwal Chhetri, M.; Vo, Q. Bao.; Kowalczyk, R.; Smari, Waleed; Fiore, Sandro; Trinitis, Carsten; Ranjan, Rajiv; Buyya, Rajkumar; Nepal, Surya; Georgakopulos, Dimitrios
Summary Cloud computing offers a realization of SOA in which IT resources are dynamically provisioned as services to consumers using flexible provisioning and pricing models. When provisioning such services, providers and consumers must first agree over the service usage terms and conditions, which are captured in Service Level Agreements (SLAs). In this paper, we propose a policy‐based framework with corresponding models, mechanisms and tools for the automated establishment of SLAs in open, diverse and dynamic cloud environments. The Automated SLA Management framework allows entities to specify their requirements and capabilities, and preferences over them in a flexible and expressive manner. It also supports multiple interaction models for SLA establishment, giving consumers and providers the flexibility to select the one that is most appropriate in a given context, while simultaneously participating in multiple concurrent SLA interactions using different interaction models. As part of the framework, we define a formal model for the underlying policies, a corresponding physical model WS‐SLAM that extends WS‐Policy and a reference architecture that can be easily implemented. We validate the practicability of our framework through the Smart CloudPurchaser prototype that can automatically purchase computing resources from Amazon EC2 under different scenarios and contexts. Copyright © 2013 John Wiley & Sons, Ltd.